Implants Placement in Contact with Dental Tissue: A Potential Paradigm Shift? Systematic Literature Review - Labidi, Amel; Bekri, Sana; Mansour, Lamia; Ghoul-Mazgar, Sonia (European Journal of Dentistry, 2019)
The aim of this study was to explore the literature for clinical and histological data of an unconventional treatment with implants placement in contact with dental tissue (IPICDT) and to try to clarify its indications and surgical procedure particularities.Relevant publications published until May 2019 on the IPICDT were thoroughly reviewed. Search strategy was developed using a controlled vocabulary combination.Medline’s exploration and manual research identified 397 articles; 15 of these were selected after screening. IPICDT was indicated in three clinical situations: impacted teeth, ankylosed teeth, or residual roots. Clinical and radiological follow-up were satisfied except for implants placed in contact with (and not through) roots. Histological analysis revealed different mineralized tissues formed on the implant surface: cementum on removed implants in human and osteodentin on implants placed in contact with animal teeth dentin and pulp. These findings were described as new concept of implants’ “Mineral integration.”According to this study, the follow-up results of implants placed in contact with roots were controversial. Some implants were stable and others were either removed or kept and disinfected after root extraction because of bacterial infection. However, implants placed through ankylosed or impacted teeth were stable. These findings suggest that the clinicians have to be cautious when applying this unconventional approach. Further studies are recommended to explore its long follow-up. It is also interesting to explore this technique in cases of syndromic dental diseases with several impacted teeth (such as cleidocranial dysplasia; or amelogenesis imperfecta).
Keywords: dental implants; tooth, impacted; tooth root; tooth ankylosis; prosthodontics